Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat pada Pasien Skizofrenia di Poliklinik Rawat Jalan Rumah Sakit Jiwa Aceh - Nailul Faiza; Urip Pratama; Nurul Amna (Lembaga Pengembangan Kinerja Dosen, 2024)
Family support is one of the main factors in the process of medication support adherence of schizophrenic patients. So the patient's health can be maintained longer. This study aims to analyze the correlation between family support and medication adherence of schizophrenic patients in the Polyclinic of Aceh Mental Hospital. A quantitative survey with an analytical design using a cross-sectional approach is employed in this research. The data was gathered from 83 respondents chosen using a purposive sampling technique. The data collection was conducted from July 22nd - 30th, 2024. A family support instrument and The Morisky Medication Adherence Scale (MMAS-8) were used for the data collection technique. Univariate and bivariate analyses are used to analyze the data. The result shows that 45 respondents (54, 2%) had good family support, and 58 respondents (69, 9%) had good medication adherence. These findings indicate a correlation between family support and medication adherence of schizophrenic patients in the Polyclinic of Aceh Mental Hospital with a ρ-value of 0,000. This study recommends that families with schizophrenia maintain and or increase supervision by providing support for medication adherence.